Analysis of Readiness for Implementing Electronic Medical Records Using the DOQ-IT Method - Yana, Wa Ode Alma; Muzuh, Mega Ermasari; Sinta, Niska Salsiani (International Journal of Multidisciplinary Learners, 2025)
This study aims to evaluate the readiness of the Wajo Community Health Center to implement Electronic Medical Records (RME). The background of this reseaech is based on the importance of digital transformation in the health service system to improve the efficiency and quality of health service through digitizing medical records. The research method used is descriptive with a qualitatif approach. Data was collected through interviews, observation. The research resulths show that the readiness of the Wajo Community Health Center in implementing RME using the portable DOQ-IT method studies is the readiness aspect: human resources, organizational work culture, and infrastructure. The researh results show that the human resources at the wajo Even Community Health Center are in the”not ready” category. Work culture and organization in the “fairly prepared” category. Governance and ladership in the “ready” category. Infrastucture in the” fairly ready” category, this isdue to a lack of HR training, specific SOPs for RME have not been prepared, infrastructure support is not yet optimal. Apart from that, further socialization and education needs to be carried out regarding the importance of RME and technology. Based on these findings, it is recommended that the Wajo Community Health Center conduct an intensive and comprehensive training program for all staff, prepare and implement clear and detailed SOPs regarding the use of RME, and increase infrastructure support by adding computer eqiupment in important locations. With this step, it is hoped that the implementation of RME at the Wajo Community Health Center can more effectively improve the quality of health services. In conclusion, although the Wajo community health centers are not yet fully ready, they are on the right track towards full implementation of RME with some necessary improvements.